Perda óssea em prótese sobre implante: revisão de literatura - Silva, Cristina Ramos da [UNESP]; Gennari Filho, Humberto [UNESP]; Goiato, Marcelo Coelho [UNESP] (My University, 2011)
One of the complications that concern prosthetists is bone loss peri-implant, because the success of dental implant treatment requires long-term maintenance of hard and soft tissues around the implant. Whereby the dental implants have not only the goal of restoring function, but also the aesthetics of the patient, the bone loss peri-implant can dramatically compromise the aesthetics of rehabilitation, particularly in anterior regions. The aim of this study was to analyze and reason, through literature review, the main factors that can cause bone loss in peri-implant and possible ways to prevent it.

Uma das complicações que preocupam os protesistas é a perda óssea periimplantar, porque o sucesso do tratamento com implantes dentais requer a manutenção a longo prazo dos tecidos moles e duros em torno do implante. Como os implantes dentários não têm somente o objetivo de devolver a função, mas também a estética do paciente, a perda óssea peri-implantar pode comprometer drasticamente a estética das reabilitações, principalmente em regiões anteriores. O objetivo deste trabalho foi de analisar e discutir, por meio de revisão de literatura, os principais fatores que podem causar perda óssea peri-implantar e possíveis formas de preveni-la.
Crestal bone loss in prosthesis implant-suported: literature review
Keywords: Dental implantation; Bone resorption; Peri-implantitis; Implante dentário; Reabsorção óssea; Periimplantite